HUBUNGAN PARAMETER HEMATOLOGI DENGAN HASIL SWAB PCR PASIEN COVID-19 - May Valzon; Dona liazarti (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
The gold standard for diagnosing COVID-19 is PCR examination, but it is difficult to implement. The earliest routine laboratory examinations requested by clinicians were hematology including hemoglobin, leukocytes, platelets, ALC and NLR. This examination is inexpensive and easy to obtain. This study aims to evaluate the relationship between hematological parameters and PCR results in patients with suspected COVID-19. The study had a cross-sectional design by conducting hematological examinations on suspected Covid-19 patients undergoing PCR swabs. The study used two specimens; first, naso/oropharyngeal swab for PCR examination; second, venous blood with EDTA anticoagulant for examination of hemoglobin, leukocytes, platelets, NLR and ALC using an automated hematology equipment. Univariate analysis was performed to determine the mean and standard deviation. Independent variable data were tested by Kolmogorov-Smirnov which were then analyzed bivariately by independent t test. The mean age of the research subjects was 48.94 years. Most of the subjects who underwent PCR swab examination were women (63%) with positive PCR swab results of 88%. The mean NLR parameter was higher in patients with positive PCR than in patients with negative PCR with p value =0.025 (p<0.05). The NLR parameter was significantly higher in patients with positive PCR so that it can be used as a guideline for clinicians in the initial evaluation of patients with suspected Covid-19.